Chemical Activation of Coal Fly Ash Waste for Adsorbent Production - Mardianingrum, Putri; Ridhwan Aprilian, Muhammad; Sani; Edra Nugraha, Reva; Karaman, Novel (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Coal fly ash is a significant byproduct of coal combustion that poses environmental risks if not properly utilized. Rich in aluminosilicates and naturally porous, fly ash can serve as an environmentally friendly, low-cost adsorbent for industrial wastewater treatment. This study aims to investigate the effect of HCl concentration and activation time on the characteristics and adsorption capacity of coal fly ash as an adsorbent. Chemical activation with HCl was performed to enhance adsorption capacity by dissolving impurities, increasing pore volume, increasing surface area, and improving silica content while reducing aluminium levels. The results indicated that the HCl-activated fly ash exhibited the highest iodine adsorption value of 778.38 mg/g, exceeding the SNI standard of 750 mg/g, demonstrating excellent adsorption performance. XRF analysis revealed 78.1% SiO? and 3.96% Fe?O? contents, suggesting that HCl-activated fly ash has great potential as an effective, economical, and sustainable adsorbent for industrial wastewater treatment. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 14 : Life Below Water